Happy Feet in a Hostile World? The Future of Penguins Depends on Proactive Management of Current and Expected Threats - Ropert-Coudert, Yan; Chiaradia, Andre; Ainley, David; Barbosa, Andres; Boersma, P. Dee; Brasso, Rebecka; Dewar, Meagan; Ellenberg, Ursula; García-Borboroglu, Pablo; Emmerson, Louise; Hickcox, Rachel; Jenouvrier, Stephanie; et al. (Frontiers in Marine Science, 2019)
Penguins face a wide range of threats. Most observed population changes have been negative and have happened over the last 60 years. Today, populations of 11 of the 18 penguin species are decreasing. Here we present a review that synthesizes details of threats faced by the world’s 18 species of penguins. We discuss alterations to their environment at both breeding sites on land and at sea where they forage. The major drivers of change appear to be climate, and food web alterations by marine fisheries. In addition, we also consider other critical and/or emerging threats, namely human disturbance near nesting sites, pollution due to oil, plastics and chemicals such as mercury and persistent organic compounds. Finally, we assess the importance of emerging pathogens and diseases on the health of penguins. We suggest that in the context of climate change, habitat degradation, introduced exotic species and resource competition with fisheries, successful conservation outcomes will require new and unprecedented levels of science and advocacy. Successful conservation stories of penguin species across their geographical range have occurred where there has been concerted effort across local, national and international boundaries to implement effective conservation planning.